Physical and allelochemical cover crop effects for weed suppression - Hewitt, Alexander John (Kansas State University, 2022)
Winter annual weeds can delay soil warming, inhibit planting operations, and compete for water and nutrients resulting in yield loss of spring planted cash crop. Understanding the timing and extent of weed emergence in different cropping systems is important to producers to be able to predict occurrence and to better manage weeds. The first objective of this research was to model the emergence of winter annual weed species in two different cropping systems based on the accumulation of thermal time. Results show that winter annual weed species composition and emergence timing can vary significantly between locations and are highly site-specific. Certain weeds such as henbit had predictable and consistent emergence timings across years in a no-tillage system in eastern Kansas but was more variable in southeast Kansas. This information can be used by farmers for weed management decisions, such as timing of control methods. The use of cover crop monocultures and mixes were evaluated for their physical and chemical weed suppressive capabilities. The second objective was to assess the levels of physical weed suppression by each cover crop treatment through weed biomass and weed density at the time of cover crop harvest. Cover crop monocultures and mixes composed entirely or mostly of aggressive grass species were found to be the most weed suppressive due to their high biomass accumulation. Certain varieties of cereal rye, annual ryegrass, winter oat, and mixes containing oat and ryegrass were found to be the highest biomass producers. Overall, cover crops provided superior weed control relative to a fallow with herbicide treatment that had no residual activity. Fertility regimes can impact cover crop biomass production and influence their allelopathic potential. The third objective was to investigate the role of nitrogen and sulfur fertilizers on cover crop weed suppression through allelopathy by conducting a weed seed germination bioassay. The results indicate that higher amounts of cover crop residues can potentially result in greater levels of weed suppression through inhibition of seed germination. Increasing soil fertility may decrease the allelopathic potential of cover crops, but can increase their biomass production, still resulting in adequate weed control.
Keywords: Cover crop; Weed suppression; Weed emergence; Allelopathy